Efektivitas Teknik Phonetic Drills dalam Meningkatkan Pengucapan Bahasa Inggris - Mutiara Sofa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of the Phonetic Drills technique in improving English pronunciation skills. Based on an in-depth literature review, Phonetic Drills is recognized as an effective method for training English pronunciation, especially for non-native speakers. This technique focuses on repetitive practice to enhance the accuracy of pronouncing difficult phonemes in English, such as the differences in vowel and consonant sounds that do not exist in the speaker's native language. This study identifies various types of Phonetic Drills, such as Minimal Pairs Drill, Repetition Drill, Chaining Drill, Tongue Twister Drill, Word Stress and Sentence Stress Drill, and Shadowing Drill, as well as explores the teaching theories of pronunciation underlying their use. Through the literature review, this study analyzes several previous studies on the use of Phonetic Drills in English language learning. The findings indicate that this technique is effective in improving pronunciation, particularly in terms of intonation, stress, and clarity of speech. However, there are challenges in its implementation, such as student boredom due to repetitive exercises and the difficulty in adjusting the technique to students' varying levels of ability. Students' perceptions of this technique show positive responses, although some experience difficulties in the initial stages of implementation. This study concludes that the Phonetic Drills technique can significantly improve English pronunciation, but it should be integrated with other methods to address its limitations. Regular and creative use of this technique is highly recommended to accelerate students' pronunciation development. Suggestions for further research include conducting studies with a larger sample and a longer duration to explore the effectiveness of this technique in various learning contexts.